(3MOjbI GdQjGMjf aj WHbGJ eTGjNfG GdeSfOjfs - (3GdHQecj , eMeO Hf gHI Gddg, JGL GdOjfs
(3ChdgG (B:s
(3Gddge dG Sgd EdG eG LYdJg SgdkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B89s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B115 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI CSYO GafOi (B(2196) s
Keywords: (3GdJGQjNs